Réponses

  • Utilisateur Brainly
2014-03-24T18:55:16+01:00
Factoriser (3x+2)²-(5-2x)(3x+2)
=(3x+2)(3x+2-5+2x)
=(3x+2)(5x-3)
Meilleure réponse !
2014-03-24T18:57:43+01:00
Factoriser :

(3x + 2)² - (5 - 2x) (3x + 2)
(3x + 2) (3x + 2 - 5 + 2x)
(3x + 2) (5x - 3)


Développer :

(3x + 2)² - (5 - 2x) (3x + 2)
9x² + 12x + 4 - (15x + 10 - 6x - 4)
9x² + 12x + -15x - 10 + 6x + 4
9x² +3x - 2

Pour le developper on fait comment stpp tu peux m'aidez
(3x + 2)² - (5 - 2x) (3x + 2) = 9x² + 12x + 4 - (15x + 10 - 6x - 4) = 9x² + 12x + -15x-10+6x+4
=9x² +3x-2
Merci beaucoup
Avec plaisir :)
=)